Iphinoe indenticulata sp. nov. (Crustacea: Cumacea: Bodotriidae), a new Korean cumacean - Kim, Sung-Hyun; Kim, Young-Hyo (Zootaxa, 2020)
A new species of Cumacea belonging to the genus Iphinoe Bate was collected from the Yellow Sea in Korea. The new speices Iphinoe indenticulata sp. nov. resembles I. sagamiensis Gamô, 1962 in the shape of carapace and the type of setae on the uropod peduncle. However, the new species is distinguished from congeners by having only setules on dorso-median carina of carapace. Also, the number of setae of uropodal peduncle and endopod is different from the I. sagamiensis. The new species is described with full illustration including mouthparts. A key to the Korean Iphinoe species is also provided.